Romanian insurance business trends and the International crisis effects on it - Joldes , Cosmin; Horobet, Alexandra (Applied Studies in Agribusiness and Commerce, 2009)
Is it interesting a 2 billion euro insurance market for the “old” Europe? “Not very much” one may say considering this figure represents no more than 16% of the insurance turn-over in the case of the most recent entry in the Romanian market, Groupama.The answer is still not as simple as that because “interesting” in business terms is not only about today, but very much about tomorrow. By the end of 2007 it was obvious that the Romanian insurance market is far from calming down. Not only that for the time being change is still the main real constant in use, but figures show that the market environment becomes more challenging than ever these days. The market situation showed that this allegation it was by that time more likely to be true than ever.